Pengaruh Pelatihan Dan Motivasi Terhadap Kualitas Kinerja Karyawan Pada PT. Citra Indojaya Perkasa Jakarta Utara - Marwah Nurinayah; Seno Sudarmono Hadi; Irwin Ananta Vidada (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This research was conducted to determine the effect of training and motivation on the performance quality of the security guard division employees at PT. Citra Indojaya Perkasa, North Jakarta. This research is a type of causal research that implements a statistical quantitative approach. The research sample consisted of thirty employees working in the security guard division. The Likert scale questionnaire was used in this study. The findings from this study reveal that training and motivation have a positive and significant impact on the quality of employee performance in the security division of PT. Citra Indojaya Perkasa in North Jakarta. The results of testing the hypothesis explained that on the performance training variable, the value of tcount (10.058) > ttable (2.052) with a significance level of Training (X1) on the quality of employee performance (Y) was 0.001 <0.05. Therefore, H0 is rejected (Ha is accepted), which indicates that performance training has a positive and significant impact on performance quality. Likewise, on the motivational variable, the value of tcount (3.657) > ttable (2.052) the significance level of motivation (X2) on the quality of employee performance (Y) is 0.001 <0.05. Therefore, H0 is rejected (Ha is accepted), which indicates that motivation also has a positive and significant effect on the quality of employee performance.